Prevalence and climatic influence on hemoparasites of cattle and sheep in Mosul, Iraq (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Hemoparasitism is a condition commonly found in animals and it exerts negatively on the health, production, reproduction, and performance of the affected animals. This study is aimed at determining the prevalence of different hemoparasites affecting cattle and sheep in Mosul, Iraq, and to deduce the effect of climatic factors on the occurrence of these hemoparasites.Materials and Methods: Blood samples from cattle and sheep that were submitted to the Parasitology Laboratory of the Veterinary Hospital of Ninavah between 2008 and 2018 were examined for the presence of blood parasites using the thin blood smear preparation. Data were analyzed using percentages (%), tabulations, and graphs. Spearman’s rank correlation coefficient was used to measure the strength of association between the occurrence of hemoparasites of cattle/sheep and each climatic variable.Results: Anaplasma spp. Babesia spp. and Theileria spp. were the hemoparasites detected among cattle and sheep in the study, with Theileria spp. been the most prevalent among cattle, while Anaplasma spp. was the most prevalent among sheep. There was no distinct pattern in the yearly and monthly prevalence of these hemoparasites among cattle and sheep. Rainfall and relative humidity negatively influenced the occurrence of hemoparasites infections, while temperature favored their occurrences.Conclusion: This study appears to be the first to evaluate the correlation between climatic variables and the prevalence of hemoparasites of cattle and sheep in Mosul, Iraq. Climatic variables influenced the abundance of hemoparasites of cattle and sheep in the study area. The outcome of this study will add to the existing knowledge on the effect of climatic factors on the occurrence of parasitic diseases of ruminants in Middle East.J. Adv. Vet. Anim. Res., 6(4): 492-498, December 2019